Nutrient Dynamics in the Deltaic Floodplain of the Lower Parana River - Bonetto, Carlos Alberto (1994)
Fil: Bonetto, Carlos Alberto. Instituto de Limnología Dr. Raúl A. Ringuelet (ILPLA). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina